Added value of dynamic MRI in assessment of cervical spondylodegenerative diseases - Menna Ahmad Mohamed Abdalhak; Hossam Mousa Sakr; Mennatallah Hatem Shalaby; Shaimaa Elmetwally El diasty (The Egyptian Journal of Radiology and Nuclear Medicine, 2023)
Abstract Background Magnetic resonance imaging (MRI) is an effective imaging tool for diagnosing spinal disorders. With a high degree of sensitivity and specificity, it gives vital information on the spinal cord, nerve roots, intervertebral discs, and ligamentous structures inside the spine. Dynamic MRI may image patients in flexed and extended postures, showing abnormalities undetected by static MRI studies. It allows for a more complete investigation of each patient and a better knowledge of the real nature of the pathology. Imaging the spine in extension and flexion, or putting the spine in pain, may help spine surgeons improve their diagnostic accuracy. We aimed to assess the diagnostic value of flexion–extension sagittal T2 (Dynamic MRI) for patients with cervical spondylodegenerative diseases. Results We found that more spinal canal stenosis levels were detected on extension position MRI compared to a neutral position (128 vs. 133 MUHLE classification system grade 0, 38 vs. 63 MUHLE grade 1, 31 vs. 13 MUHLE grade 2, 13 vs. 1 MUHLE grade 3), which was statistically significant according to MUHLE among total disc levels, with p value < 0.05. While more spinal canal stenosis levels were detected on flexion position MRI than in neutral position (134 vs. 133 MUHLE grade 0, 49 vs. 63 MUHLE grade 1, 23 vs. 13 MUHLE grade 2, 4 vs. 1 MUHLE grade 3), which was statistically insignificant according to MUHLE among total disc levels (p value > 0.05). Conclusions Flexion and extension MR imaging demonstrates additional information using a non-invasive technique concerning the dynamic factors in the pathogenesis of cervical spondylodegenerative diseases. DMRI identifies a significant percentage of increased spinal stenosis especially at extension position more than at neutral and flexion positions. So, we recommend to include extension DMRI in investigations for diagnosis and management plans of cervical spondylodegenerative diseases.